Enhancing the role of teachers' trade unions in the culture of teaching and learning - Kubheka, Enoch Sihle Banana (University of the Free State, 2022)
The main objective of this study was to enhance the role of teachers’ trade unions in COLT. The underlying principle was being informed by the noticeable neglect of learners when members of a teacher trade union attend to their union matters during the official teaching and learning time. This has developed into a propensity which gradually meddles with the constitutional provisions of the existing rights of children regarding their interest, notwithstanding the rights of union members as stipulated in the South African Constitution. Following a qualitative research approach, this study adopted the Participatory Research (PR) as a methodology. PR is a self-conscious way of empowering people to take effective action toward improving conditions in their lives. Participatory researchers caution against either dichotomy: “They know, I don’t know.” Or “They don’t know, I know.” Instead, PR offers a partnership: “We both know some things; neither of us knows everything. Working together, we will both know more, and we will both learn more about how to know.” Basically, PR promotes collaboration amongst participants in and of the study. Research paradigm that my study used was Critical Theory which is transformative in nature as such helping the oppressed children in schools to be liberated from teachers’ trade unions activities during COLT. Theoretical framework used was Critical Emancipatory Research helping to understand those without power and affording voice to those without one, was one of the main purposes of CER. Purposeful participant selection was used to select the population and sample all participants stating the reason why they are appropriate for the success of the research. Data collection instrument was interviews to collect data from the participants. For data analysis, Critical Discourse Analysis was used for analysing, interpreting, drawing findings, making conclusions and reporting. My dissertation’s findings were to advance and enhance the existing body of knowledge relating to the role of teachers’ trade unions in COLT. It was also to add new information about my dissertation – thus addressing the gaps in the existing knowledge, like the neglect of the education policies and/or the non-knowledge thereof. Some of the recommendations of the study were for the officials of the Department of Education to familiarise themselves more with the employer’s policies for effective implementation and unions need to regularly induct their new members into their constitutions and many more in the last chapter. The conclusions about the implications of my dissertation was to enhance the relationship between teachers’ trade union members and the Department of Education regarding the interest of the child. This was to diminish and limit the meddling behaviour which the teachers’ trade union members demonstrate when leaving learners unattended during official notional time to attend to their own interests. It was going to benefit all stakeholders in understanding both negative and positive repercussions that teachers’ trade unions have on the education system, but more specifically in COLT.
Dissertation (M.Ed. (Education Management and Leadership))--University of the Free State, 2022
Keywords: Culture; trade union; role; teaching; learning; enhancing